Identification Of Helicobacter Pylori In Gastritis And Escherichia Coli In Gastroenteritis Using The Electrophoresis Method - Rahmawati; Juni Masna Santi Giawa; Yudhistira (Medistra Medical Journal (MMJ), 2026)
Gastritis and gastroenteritis are common digestive disorders often associated with infections caused by the bacteria Helicobacter pylori (H. pylori) and Escherichia coli (E. coli). Rapid and accurate diagnosis is crucial for determining appropriate management, but conventional methods still have limitations in terms of sensitivity and turnaround time. This study aims to identify the presence of H. pylori DNA in gastritis patients and E. coli DNA in gastroenteritis patients using electrophoresis following DNA amplification via PCR (Polymerase Chain Reaction). This is a laboratory experimental study utilizing 10 patient blood samples, comprising 5 patients diagnosed with gastritis and 5 patients with gastroenteritis. The research procedure included DNA extraction, amplification of target genes (ureA for H. pylori and stx1 for E. coli), and visualization of the results using agarose gel electrophoresis. The results showed that of the 5 samples from gastritis patients, 4 samples (80%) exhibited a 294 bp DNA band, indicating the presence of the H. pylori gene. Meanwhile, all gastroenteritis patient samples (100%) showed a 302-bp DNA band, indicating the presence of the E. coli gene. The electrophoresis results showed clear and consistent DNA bands in identifying both bacteria. The conclusion of this study indicates that the PCR-based electrophoresis method is effective in rapidly and accurately detecting the presence of H. pylori and E. coli in clinical samples, thus having the potential to serve as a reliable molecular diagnostic method to support the diagnosis of gastritis and gastroenteritis.